2015
DOI: 10.1007/s10397-015-0912-6
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative transvaginal sonography: a novel approach for localization of deeper myomas during laparoscopic myomectomy

Abstract: The aim of this study is to assess the use of intraoperative transvaginal ultrasonography (TVS) to locate deep myomas that were not identified on laparoscopic view. The design of this study is a prospective observational study. This study was conducted in private Advanced Endoscopy and Infertility Treatment Centre, Kerala, India. The study comprised of 84 patients who underwent laparoscopic myomectomy from January 2011 to December 2013 in whom intraoperative TVS was used as an intervention. The number of addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The use of US allowed a successful myomectomy to be performed, preventing the need to convert to open surgery [9]. These benefits have been further investigated and reproduced in a number of prospective studies which confirm the ability of IOUS (endoscopic or transvaginal) to accurately localize and remove additional myomas that are not visible laparoscopically [43,44]. A recent study investigating the use of IOUS laparoscopically and transvaginally found LUS was more effective in localizing residual fibroids following laparoscopic myomectomy [45].…”
Section: Us Guidance In Laparoscopic Proceduresmentioning
confidence: 95%
“…The use of US allowed a successful myomectomy to be performed, preventing the need to convert to open surgery [9]. These benefits have been further investigated and reproduced in a number of prospective studies which confirm the ability of IOUS (endoscopic or transvaginal) to accurately localize and remove additional myomas that are not visible laparoscopically [43,44]. A recent study investigating the use of IOUS laparoscopically and transvaginally found LUS was more effective in localizing residual fibroids following laparoscopic myomectomy [45].…”
Section: Us Guidance In Laparoscopic Proceduresmentioning
confidence: 95%
“…Previous studies have demonstrated the usefulness of IUS in identifying the location of deep myomas and the best site for uterine incision during laparoscopic myomectomy 2 , and in evaluating residual myomas after surgery 3,4 . Other studies have shown that, during open myomectomy, IUS with direct application of the probe onto the uterine serosa is more efficient than palpation in evaluating residual myomas at the end of the surgery 5 .…”
Section: Intraoperative Ultrasound Assistance During Myomectomy In Prmentioning
confidence: 99%
“…Recently, intraoperative ultrasound examination has been proposed in this setting as a useful method to guide the surgeon during myomectomy. Paul et al demonstrated that intraoperative transvaginal ultrasound is helpful to the surgeon for identifying deeper myomas making the surgery more effective [4]. Other authors reported cases of an intraoperative ultrasound using a laparoscopic probe to guide surgeon to identify the correct placement of the uterine incision during laparoscopic myomectomy [5,6].…”
mentioning
confidence: 99%